Heterogeneity of first‐line palliative systemic treatment in synchronous metastatic esophagogastric cancer patients: A real‐world evidence study. Issue 7 (24th August 2019) - Dijksterhuis, Willemieke P.M.; Verhoeven, Rob H.A.; Slingerland, Marije; Haj Mohammad, Nadia; de Vos‐Geelen, Judith; Beerepoot, Laurens V.; van Voorthuizen, Theo; Creemers, Geert‐Jan; van Oijen, Martijn G.H.; van Laarhoven, Hanneke W.M.
Abstract : The optimal first‐line palliative systemic treatment strategy for metastatic esophagogastric cancer is not well defined. The aim of our study was to explore real‐world use of first‐line systemic treatment in esophagogastric cancer and assess the effect of treatment strategy on overall survival (OS), time to failure (TTF) of first‐line treatment and toxicity. We selected synchronous metastatic esophagogastric cancer patients treated with systemic therapy (2010–2016) from the nationwide Netherlands Cancer Registry ( n = 2, 204). Systemic treatment strategies were divided into monotherapy, doublet and triplet chemotherapy, and trastuzumab‐containing regimens. Data on OS were available for all patients, on TTF for patients diagnosed from 2010 to 2015 ( n = 1, 700), and on toxicity for patients diagnosed from 2010 to 2014 ( n = 1, 221). OS and TTF were analyzed using multivariable Cox regression, with adjustment for relevant tumor and patient characteristics. Up to 45 different systemic treatment regimens were found to be administered, with a median TTF of 4.6 and OS of 7.5 months. Most patients (45%) were treated with doublet chemotherapy; 34% received triplets, 10% monotherapy and 10% a trastuzumab‐containing regimen. The highest median OS was found in patients receiving a trastuzumab‐containing regimen (11.9 months). Triplet chemotherapy showed equal survival rates compared to doublets (OS: HR 0.92, 95%CI 0.83–1.02; TTF: HR 0.92, 95%CI 0.82–1.04) but significantly more grade 3–5 toxicity than doublets (33% vs . 21%, respectively). In conclusion, heterogeneity of first‐line palliative systemic treatment in metastatic esophagogastric cancer patients is striking. Based on our data, doublet chemotherapy is the preferred treatment strategy because of similar survival and less toxicity compared to triplets. Abstract : What's new? Metastatic esophagogastric cancer can't be cured, but palliative therapy can improve patients' quality of life and survival. However, there's no consensus regarding the optimal first‐line palliative systemic therapy for metastatic esophagogastric cancer. Here, the authors evaluated real‐world use of first‐line systemic treatments. The retrospective study included a cohort of 2, 204 metastatic patients and found 45 different treatment regimens administered. Patients that received doublet and triplet chemotherapy had similar survival, with triplet patients experiencing higher toxicity. Monotherapy produced significantly worse overall survival and only modest reduction in toxicity. These findings support doublet therapy as the optimal first‐line treatment strategy.